(3GdeSJWGH aj JGQjN YdeGA GdRjOjI GdCWjGHs - (3jMji Hf GdMSjf Hf GdbGSe Hf eMeO, GHf GdbGpSe,J (B1099 (3g` s
(3ChdgG (B:s
(3hHYO , aEfg deG cGf ai Yde GdJGQjN ahGFO LdjdI YOjOI , hYHQ fGaYI MejOI s
(3BNQgG (B:s
(3hbO QCjfG Cf fNJe GdcJGH ai gPG GdehVY hCfG CSJZaQ Gddg GdYXje eeG hbY ajg ef Sgh s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJs
(3ajgG HjGVs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs